Implantation of Polycaprolactone (PCL) Thread Increased Dermal Collagen of Old Female Wistar Rats (Rattus Norvegicus) More Than Polydioxanone (PDO) Thread - Junivan Lindra; Wimpie Pangkahila; Anak Agung Gde Putra Wiraguna (Fakultas Kedokteran Universitas Udayana, 2021)
Introduction: Wrinkles and sagging are the sign of skin aging. Threadlift using polydioxanone (PDO) and polycaprolactone (PCL) can increase the amount of collagen. This study aimed to study which thread is better to induced collagenesis. Methods: This study used a posttest-only control group design. The subjects were 30 Wistar rats, healthy, female, age 16-18 months (human equivalent age 45 years), the body weight of 160-180 grams which were divided into three groups (n = 10). The negative control group (P0) was not given any treatment, the positive control group (P1) was treated with 27G needle pierced, 60 mm with 3 PDO threads horizontally in the dermal layer, treatment group (P2) was treated with 27G needle pierced, 60 mm with 3 PCL threads horizontally in the dermal layer. After 4 weeks, a 5x5mm biopsy was performed on the skin and histopathological preparations were made with Sirius Red staining. Results: The results showed that the amount of collagen in the P0 group was 75.0±1.51, in the P1 group was 82.3 ± 1.49, while in the P2 group was 86.0 ± 1.22 (p <0.001). The LSD test showed that there were differences between the P1 group and the P2 group (p <0.001), where the amount of dermal collagen in the PCL group was higher compared to the PDO group. Conclusion: It can be concluded that the implantation of polycaprolactone (PCL) thread increased dermal collagen of old female Wistar rats (Rattus norvegicus) more than polydioxanone (PDO) thread.